A multimodal approach to ankle instability: interrelations between subjective and objective assessments of ankle status in athletes - Golditz, Tobias C.; Welsch, Goetz H.; Pachowsky, Milena; Hennig, Friedrich F.; Pfeifer, Klaus; Steib, Simon (Journal of orthopaedic research, 2016)
The aim of this retrospective cohort study is to investigate the association between different subjective and objective assessments of ankle function in a population of athletes with or without functional ankle instability (FAI). 29 athletes with a history of ankle spraining were divided into two groups according to their ankle status: 16 with FAI (initial ankle sprain with residual functional instability) (age 24.6 ± 3.1 years), and 13 COPERS (initial ankle sprain without residual instability) (age 25.3 ± 4.4 years). The assessment of each individual's ankle function was based on three approaches: The “functional-ankle-ability-measure” (FAAM) assessing subjective ankle functionality, measures of sensorimotor control as objective functional measurements and MRI-based T2-mapping as a quantitative marker of compositional joint status. Pearson's product-moment-correlation coefficient, student's t-test and analysis-of-variance were used for statistical analysis. Significant group differences existed for subjective ankle function (FAAM, p = 0.04) and MRI-data mainly in the medial compartment of the ankle joint (p ≤ 0.05). We found unique associations between T2-mapping results and sensorimotor scores in the COPER (r = −0.756-0.849), and “FAI”-group (r = 0.630-0.657). The location and magnitude differed between groups. No correlations existed between these measures and the FAAM. This exploratory study provides preliminary evidence for potential interrelations between various diagnostic measures of ankle function and structure in individuals with and without FAI. We found associations between MRI-results and selected measures of sensorimotor control, indicating a potential link between loss of ankle function and early joint degeneration. Despite these interrelations, each of the different assessment options appears to contain unique information on ankle functionality important in a clinical assessment. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:525-532, 2016.